FINANCIAL DIFFICULTIES MEDIATED BY LIQUIDITY AND MODERATED BY SALES GROWTH: FINANCIAL DIFFICULTIES MEDIATED BY LIQUIDITY AND MODERATED BY SALES GROWTH - Kurniawati, Endang Kurniawati; Mohklas, Mohklas; Nurdiyanto, Ahmad Dwi Nurdiyanto; Prabowo, Janitra Prabowo; Yusroni, Nanang Yusroni (Universitas Wahid Hasyim Semarang, 2024)
When companies are unable to meet their financial obligations, such as debt payments or operational costs, they often face financial difficulties. They usually occur due to low profitability, inadequate liquidity, and declining sales, all of which can lead to bankruptcy if not addressed promptly. With liquidity as a mediating variable and sales growth as a moderating variable, this study examines how profitability impacts financial distress. Using secondary data, this research aims to determine how profitability and liquidity affect financial distress and how sales growth either helps or worsens this relationship in property and real estate companies listed on the Indonesia Stock Exchange from 2021 to 2023. In this study, a purposive sampling method was used, and a total of 26 companies were sampled. Hypothesis testing, path analysis, and moderated regression analysis (MRA) were used as testing methods, and all of this was conducted with the assistance of SPSS 25 software. Research results indicate that profitability significantly affects liquidity, but does not significantly affect financial difficulties. Liquidity also does not significantly affect financial distress, and sales growth does not serve as a mediator between profitability and financial difficulties.